THE PROBLEM OF THE QUALITY PROVIDING OF THE RAILWAY TRANSPORT OBJECTS - Pshinko, O. M.; Netesa, M. I.; Krasniuk, A. V. (Science and Transport Progress, 2008)
The issues of providing the quality of construction of railway transport objects, organization of works on putting them into operation are presented.